Ginseng: a promising neuroprotective strategy in stroke - Rastogi, Vaibhav; Santiago-Moreno, Juan; Doré, Sylvain (Frontiers in Cellular Neuroscience, 2015)
Ginseng is one of the most widely used herbal medicines in the world. It has been used in the treatment of various ailments and to boost immunity for centuries; especially in Asian countries. The most common ginseng variant in traditional herbal medicine is ginseng, which is made from the peeled and dried root of Panax Ginseng. Ginseng has been suggested as an effective treatment for a vast array of neurological disorders, including stroke and other acute and chronic neurodegenerative disorders. Ginseng’s neuroprotective effects are focused on the maintenance of homeostasis. This review involves a comprehensive literature search that highlights aspects of ginseng’s putative neuroprotective effectiveness, focusing on stroke. Attenuation of inflammation through inhibition of various proinflammatory mediators, along with suppression of oxidative stress by various mechanisms, including activation of the cytoprotective transcriptional factor Nrf2, which results in decrease in reactive oxygen species, could account for its neuroprotective efficacy. It can also prevent neuronal death as a result of stroke, thus decreasing anatomical and functional stroke damage. Although there are diverse studies that have investigated the mechanisms involved in the efficacy of ginseng in treating disorders, there is still much that needs to be clarified. Both in vitro and in vivo studies including randomized controlled clinical trials are necessary to develop in-depth knowledge of ginseng and its practical applications.